A notificação compulsória dos atos de violência contra a pessoa velha no ambiente da saúde: limites e desafios na cidade de Palmas - Paula, Cynthia Assis de (Universidade Federal do Tocantins, 2016)
The goal of our research is to analyze the mandatory reporting of violence against old people for health services, as the instrument for combating violence and its implications for the protection and promotion of human rights in the senior living in Palmas city. The research used data collected between 2009 and 2015extracted from the Compulsory Notification Form of Violence, known to form sinan, and contained in the computerized database Notifiable Diseases Information System (Sinan-NET). This dissertation discusses historical aspects of old age and brings to the conceptual debate the old signs, old age and aging in a historicalpolitical and cultural study. Explains the concepts of old age in contemporary society and portrays the living conditions of old people in Brazil as well as outline the milestones of your protection with characterization and representation of the safety net. The bibliographical, documentary and field research under the deductive method and critical-dialectical approach took advantage of laws, norms, plans, proceedings and deliberations of national elderly conferences, as well as texts and manuals produced by the Department of Human Rights and the Ministry of Health, doctrines, scientific articles, doctoral dissertations and master's thesis. The search result has enabled the generation of indicators shown in four tables and 21 charts. By analyzing the data of violence is identified underreporting and their possible causes as well as the profile of the victim and the aggressor in Palmas City. Among the key findings is the proposed readjustment of the notification form , the need for greater attention to training processes of reporters and agents to create a multidisciplinary environment for aging monitoring in Tocantins